Transformasi Pendidikan Pesantren dalam Perspektif KH. Sahal Mahfudh - Rohani Shidiq (Edukasia Islamika, 2017)
This current study highlights the paradigm of KH. MA Sahal Mahfudh’s perspective on the concept of social fiqh (a worthy alternative to international Islamic jurisprudence) and the transformation of education in pesantren (Islamic boarding school). It was qualitative study by conducting library research. The findings promote that in his perspective, the education in pesantren is not merely Islam-oriented (tafaqquh fi al-din), but also plays a pivotal role in the students’ lives as well as the transformation into a shalih (good) and akram (noble) society, which is in line with the leadership principles of human beings. In relation to the social fiqh, KH. Sahal has asserted that fiqh does not refer to the concept of dogma and norms, but the active and progressive one so that fiqh always develops from time to time. It implies that fiqh does not demonstrate the stagnancy of its implementation in life. Meanwhile, the transformation of education in pesantren is generally viewed that this kind of boarding school functions as an institution of tafaqquh fi al-din, yet it is integrated with the content of additional learning materials. This content attempts a system of education that provides the students with various life skills as well in regard to the era of modernization. In KH. Sahal’s point of view, the transformation of education in pesantren can be identified in detail through the transformation of education components, namely: institution, organization, curriculum, methodology, and teachers